2009
DOI: 10.1038/sj.bjc.6605466
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and squamous cell carcinoma of the conjunctiva

Abstract: BACKGROUND: Squamous cell carcinoma of the conjunctiva (SCCC) is associated with HIV-related immunosuppression, but human papillomavirus virus (HPV) is also suspected to have a role. We carried out a case -control study to assess the role of cutaneous and mucosal HPV types in SCCC, conjunctival dysplasia, and their combination (SCCC/dysplasia) in Uganda. METHODS: We compared HPV prevalence in frozen biopsies from 94 SCCC cases (79 of whom were found to be HIV-positive), 39 dysplasia cases (34 HIV-positive), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 17 publications
1
68
0
1
Order By: Relevance
“…Human papillomavirus and human immunodeficiency virus have also been cited as possible cofactors in OSSN that may influence the prognosis. 3,[18][19][20] Recurrence developed in 17% of 48 patients herein with follow-up data, which is similar to that in other studies (17%-41%). 1,7 Larger tumors (2 cm) and those with a diffuse growth pattern had a higher risk of recurrence.…”
Section: Correlation Of Clinicopathological Features With Recurrence-supporting
confidence: 80%
“…Human papillomavirus and human immunodeficiency virus have also been cited as possible cofactors in OSSN that may influence the prognosis. 3,[18][19][20] Recurrence developed in 17% of 48 patients herein with follow-up data, which is similar to that in other studies (17%-41%). 1,7 Larger tumors (2 cm) and those with a diffuse growth pattern had a higher risk of recurrence.…”
Section: Correlation Of Clinicopathological Features With Recurrence-supporting
confidence: 80%
“…2 HPV infection is present in up to half of the cases. 36 There appears to have been no reduction in the steady increase in incidence in Kampala, despite modest declines in HIV prevalence, and increasing use of ART. It has been observed that in addition to human papilloma virus, sunlight exposure in equatorial region is a major aetiological factor of SCCC in patients with severe immunesuppression.…”
Section: Epidemiologymentioning
confidence: 99%
“…In African case series there is a high prevalence of DNA HPV 6 and 11, but not HPV 16 and 18 (Verma et al, 2008). On the other hand, in a series reported recently in Uganda, HPV 5 and 8 were the most common in nearly half of OSSN (Ateenyi-Agaba, et al, 2010). We have detected the presence of DNA HPV type 11.…”
Section: Human Papilloma Virus (Hpv) Detectionmentioning
confidence: 49%